Social Interaction Potential and the Spatial Distribution of Face-to-Face Social Interactions. (December 2014) - Farber, Steven; Neutens, Tijs; Carrasco, Juan-Antonio; Rojas, Carolina
This paper investigates the spatial distribution of social activity locations. The research makes use of a social interaction potential (SIP) metric to estimate the potential for an individual to participate in a face-to-face social activity at any particular location in the city. The metric is shown to constitute a contact probability field that is sensitive to time-geographic constraints such as home locations, workplaces, and travel times. Empirical case studies drawn from samples in Ghent, Belgium and Concepción, Chile are used to evaluate the effectiveness of the SIP metric in assigning high potential scores to observed social activity episodes. Moreover, a regression model is used to estimate the marginal benefit of using successive levels of constraint detail. The results illustrate both positive and negative aspects of the SIP metric. The metric behaves very well in general; 75% of the time an observed activity location received a score in the 25th percentile. However, lower valued scores were more common in cases when the time-geographic constraints were not very strong (ie, when the commute duration was short), or when activities took place in the homes of the respondents. In the end, the results are a step towards validating the regional scale SIP metric and indicate that it may be useful in microsimulation models of daily travel and activity participation.